Measurement of non-monotonous phase changes in temporal speckle pattern interferometry using a correlation method without a temporal carrier - Tendela, Lucas Pedro (2015)
Recently, a phase evaluation method was proposed to measure nanometric displacements by means of digital speckle pattern interferometry when the phase change introduced by the deformation is in the range [0,π) rad. This method is based on the evaluation of a correlation coefficient between two speckle interferograms generated by both deformation states of the object. In this paper, we present a novel technique to measure non-monotonous displacements in temporal speckle pattern interferometry using a correlation method without a temporal carrier. In this approach, the sign ambiguity is resolved automatically due to the introduction of a function that determines the correct sign of the displacement between two consecutive speckle interferograms. The rms phase errors introduced by the proposed method are determined using computer-simulated speckle interferograms. An application of the phase retrieval method to process experimental data is also presented.